Analysis of Portable Fire Extinguishers and Evacuation Facilities Based on National Regulations - Annisa Nur Berliana; Muhammad Fadillah Zulhayudin (Periodicals of Occupational Safety and Health, 2025)
Background:       Adi Satria Abadi is a manufacturing enterprise specializing in the production of sheepskin-based golf gloves. The facility stores various hazardous substances, including chemical agents, sheepskin, and other highly combustible raw materials. Consequently, the implementation of a robust fire protection system is imperative to ensure operational safety. Given the intensive nature of production activities within the premises, an adequate fire suppression and prevention infrastructure is essential to mitigate potential fire-related risks. Method: This research employs a qualitative approach utilizing a case study design. Data collection was conducted through structured interviews with three key informants: the Occupational Health and Safety (K3) Secretary, a Human Resources Department (HRD) representative, and the Fire Emergency Response Team (Red Team). A purposive sampling technique was utilized, supplemented by direct field observations and comprehensive documentation. Results: The findings indicate that the active fire protection systems, specifically portable fire extinguishers (APAR), generally align with the Ministry of Manpower Regulation No. PER.04/MEN/1980, although certain deficiencies persist. Similarly, evacuation facilities—encompassing evacuation routes, emergency exits, corridors, and assembly points largely adhere to the Ministry of Manpower and Transmigration Regulation No. PER.16/MEN/2008, yet require further rectification. Conclusion: Therefore, it is recommended that the enterprise immediately replace corroded fire extinguishers and formulate formal organizational policies regarding evacuation facilities to effectively minimize fire hazards.